2005
DOI: 10.3354/meps288059
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of macrofaunal burrows for the microbial mineralization of pyrene in marine sediments: impact of macrofaunal species and organic matter quality

Abstract: The significance of macrofaunal burrows for microbial organic matter mineralization is well recognized. However, despite the importance of marine sediments as main sinks for organic particle-reactive contaminants such as polyaromatic hydrocarbons (PAHs), the significance of biogenic structures for microbial pollutant mineralization is largely unknown. We measured microbial mineralization of the PAH pyrene in different sediment compartments (surface, burrow and reduced bulk sediments) as a function of contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Its fate is therefore also determined by metabolization and mineraliz ation processes, and degradation product may subsequently be eliminated from burrow sediment with exhaust water facilitated by macrofaunal irrigation. Granberg et al (2005) found microbial pyrene mineralization rates to be 1.5-2.5 times higher in A. filiformis burrows compared to N. diversicolor burrows.…”
Section: Sedimentary Distribution Of ?Pyrenementioning
confidence: 84%
See 2 more Smart Citations
“…Its fate is therefore also determined by metabolization and mineraliz ation processes, and degradation product may subsequently be eliminated from burrow sediment with exhaust water facilitated by macrofaunal irrigation. Granberg et al (2005) found microbial pyrene mineralization rates to be 1.5-2.5 times higher in A. filiformis burrows compared to N. diversicolor burrows.…”
Section: Sedimentary Distribution Of ?Pyrenementioning
confidence: 84%
“…irrigation and particle mixing) is therefore an important process affecting sedimentary PAH degradation through the oxygenation of deeper sediment layers, and through the transport of contaminated particles between oxic and reduced layers (Gardner, Frez, Cichocki & Parrish, 1985, Bauer, Kerr, Bautista, Decker & Capone, 1988, Holmer, Forbes & Forbes, 1997, Kure & Forbes, 1997. and Granberg et al (2005) furthermore stress the importance of species specific bioturbation patterns for observed differences in microbial degradation and mineralization of pyrene in sediments. Although sparsely investigated, other factors suggested to affect sedimentary microbial PAH degradation are repeated PAH exposure and altered sediment organic matter (SOM) quantity and quality (ZoBell, 1946, Bauer & Capone, 1985, Cerniglia & Heitkamp, 1989.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These metabolites have in turn been shown to be difficult to use for PAHdegrading bacteria, thereby inhibiting mineralization rather than promoting it (Giessing and Johnsen, 2005). Despite this, the presence of fauna, such as polychaetes, is known to increase PAH mineralization (Gardner et al, 1979;Bauer et al, 1988;Granberg et al, 2005) through increased oxygen and nutrient fluxes due to bioturbation. Such stimulatory effects from fauna are likely to have occurred in all treatments, as meiofauna also is known to increase oxygen fluxes (Aller and Aller, 1992) Anaerobic mineralization of PAHs can also occur in sediments (Coates et al, 1997), although it is not likely to be important in this study due to the fact that the majority of the remaining 14 C in the sediment was present in the top centimeter of the sediment (average 78%, data not shown), and that the water column was continuously aerated.…”
Section: Discussionmentioning
confidence: 99%
“…Irrigated burrows often show enhanced activity of biogeochemical processes (Kristensen et al 1985, Mayer et al 1995, Papaspyrou et al 2006) and both bacteria and meiofauna are often more abundant in burrows and tubes compared with the surrounding sediment (Reise 1981, Papaspyrou et al 2006. The significance of burrow structures as sites of enhanced capacity for microbial PAH mineralization have also been documented (Chung & King 1999, Granberg et al 2005.…”
Section: Introductionmentioning
confidence: 99%